Differences in Motivation and Physical Self-Concept among Pupils of Early Primary School Age Relative to Their Level of Physical Activity - Slobodan LJ. Pavlović; Vladan M. Pelemiš; Dragan B. Marinković (University of Belgrade, Teacher Education Faculty, 2020)
Maintaining quality physical education classes, as provided for in the curriculum, encounters numerous problems and difficulties in implementation on a daily basis. Pupils' full engagement and activity in the physical education class is an important precondition for physical education to really be in the function of healthy growing up and preparation of pupils for an active lifestyle. The aim of this research was to determine the differences in the motivation and physical self-concept of pupils relative to the level of their physical activity in the physical education class. The research included 423 students from the territory of the city of Užice (aged 10 ± 1.3 years), 227 boys and 196 girls, organized in three groups according to the level of physical activity in physical education class (A-low; B-medium; C- high). A modified Self-Regulation Questionnaire (Ryan & Connell, 1989) was used to assess pupils' motivation orientations, and appropriate subscales of the Self-Perception Profile for Children measuring instrument (SPPC, Harter, 1985; rev. 2012) were used to assess physical self-concept. Physical activity (scope (number of steps) and intensity) of pupils in physical education class was measured using the CoachGear pedometer and the Suunto Memory Belt heart rate monitor. The presented results indicate the existence of significant differences among the groups of respondents of both sexes in relation to the level of physical activity of pupils of younger school age. Based on the obtained findings, it can be concluded that the expressed differences are greater in boys than in girls. The results published in this study support most of the findings indicating differences in motivation and physical self-concept. It was further determined that less active children generally show lower levels of motivation, as well as the values of the physical self-concept. The authors believe that in the planning and programming of physical education classes, emphasis must be placed on creating a favorable "climate" for teaching. Initial education of preschool and primary school teachers must be innovated in accordance with the new requirements and expectations that society puts before school physical education.